2014
DOI: 10.1074/jbc.m114.606483
|View full text |Cite
|
Sign up to set email alerts
|

Gli1 Protein Regulates the S-phase Checkpoint in Tumor Cells via Bid Protein, and Its Inhibition Sensitizes to DNA Topoisomerase 1 Inhibitors

Abstract: Background: Aberrant expression of Gli1 is observed in cancers of many tissues and is associated with aggressive disease. Results: Gli1 inhibition in tumor cells abrogates ATR-mediated Chk1 phosphorylation by down-regulating the BH3-only protein Bid and sensitizes them to camptothecin. Conclusion: Gli1 inhibition sensitizes tumor cells to chemotherapy. Significance: These results identify a novel mechanism of Gli1-mediated S-phase checkpoint regulation and therapeutic combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 70 publications
1
48
0
Order By: Relevance
“…1B). Aberrant Hedgehog (Hh)/Gli signaling is commonly associated with tumor growth, metastasis, and resistance to chemotherapy [16,19] and we previously demonstrated that ALDH1A1 regulates DNA repair and checkpoint progression to enhance resistance to platinum drugs [14]. Therefore, we examined stage 3 and 4 OC and adjacent normal tissue for expression of these proteins in addition to Rad6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1B). Aberrant Hedgehog (Hh)/Gli signaling is commonly associated with tumor growth, metastasis, and resistance to chemotherapy [16,19] and we previously demonstrated that ALDH1A1 regulates DNA repair and checkpoint progression to enhance resistance to platinum drugs [14]. Therefore, we examined stage 3 and 4 OC and adjacent normal tissue for expression of these proteins in addition to Rad6.…”
Section: Resultsmentioning
confidence: 99%
“…For clonogenic survival assays, 500 cells were plated in 6-well culture dishes in triplicate [16]. Cells were allowed to attach overnight and treated with indicated concentrations of carboplatin or vehicle control (DMSO) overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu FY et al found that the molecular mechanisms regulated by the non-canonical Hh pathway mediated through ptch1 and cyclin B1 is involved in the pathogenesis of nevoid basal cell carcinoma syndrome (NBCCS)-associated keratocystic odontogenic tumors (KCOTs) [62]. Tripathi K et al demonstrated that a novel and tumor-specific role for aberrant Gli1 in the regulation of the S-phase checkpoint that suppresses replication stress and resistance to chemotherapy [63]. Therefore, the S phase arrest may be caused by a more significant inhibition in Hh pathway induced by the combination of ATO and CYA.…”
Section: Discussionmentioning
confidence: 99%
“…Active DNA repair in normal cells will allow the cells to repair the damages and stay healthy, while active DNA repair in cancer cells will often result in repairing of chemotherapeutics induced DNA damage and induce chemoresistance. 53,54 Thus makes all the regulators of DNA repair mechanism including ROS, an important messenger for normal cell survival. Since the cells response to ROS varies based on cell type and magnitude of ROS formation, complete analysis of ROS in cells with different genetic background has to be analyzed in detail.…”
Section: Ros Induced Change In Dna Repairmentioning
confidence: 99%